The Algerian Liberal Elite and the Federal State Project in the period of 1943–1945 - safsaf, houari (The Algerian Historical Journal, 2026)
This study focuses on an important stage of the political ideology of the Algerian liberal elite during the period of World War II which began after the Allies landed in Algeria. During the years following the Anglo-American landing on the Algerian coast, the liberal elite, led by Farhat Abbas, called for an Algerian republic federally dependent on France In the midst of the World War II which contributed to the liberal elite taking the lead in the political scene and proposing the idea of establishing a federal state affiliated with France, alongside the changes that were taking place in the Algerian political sphere. This led Algerians to get acquainted with the new proposition of the liberal elite to solve the Algerian issue. Moreover, this proposal was characterised by a number of features, including Algeria's political independence, an Algerian constitution, and a parliament chosen by the entire country.